2009
DOI: 10.1177/1479972309103884
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of recent asthma symptom surveys in Iranian children

Abstract: Asthma is the most prevalent chronic disease in children. To quantify the national prevalence of asthma symptoms in Iranian children, we conducted a systematic review and meta-analysis. After internet and hand searching for population-based prevalence estimates published from 1998 to 2003 from 142 articles, dissertations and reports of research projects, 19 of them were selected. All the selected studies on children had been performed by the International Study of Asthma and Allergies in Childhood (ISAAC) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…In a review study the prevalence of asthma symptoms in different cities of Iran is reported in the range of 2.7% to 35.4%. Overall national prevalence is 13.14% [13]. This shows less prevalence of asthma symptoms in Yazd compared to national level.…”
Section: Discussionmentioning
confidence: 96%
“…In a review study the prevalence of asthma symptoms in different cities of Iran is reported in the range of 2.7% to 35.4%. Overall national prevalence is 13.14% [13]. This shows less prevalence of asthma symptoms in Yazd compared to national level.…”
Section: Discussionmentioning
confidence: 96%
“…First, we noticed that speculations regarding the role of human salivary NGF-β as presented by Laurent et al (1), and in subsequent articles (3)(4)(5)(6), seemed inconsistent with current knowledge in this area and were based, in part, on extrapolations from studies in mice. In these animals, the submaxillary salivary gland produces high concentrations of NGF-β, thought to have important local and endocrine functions (7).…”
Section: Closing the Border On A New Frontier: The Problem With Salivmentioning
confidence: 88%
“…The prevalence of major depressive disorder is increased significantly across adolescence (3). Regarding the high prevalence of asthma and mood disorders in adolescents in our area (3)(4)(5)(6), we evaluated the frequency of depression in adolescents with asthma in comparison to adolescents without asthma in the city of Zanjan, Iran.…”
mentioning
confidence: 99%
“…[20] In this regard, it is evident that the prevalence of asthma symptoms and in turn the average annual cost of asthma treatment has dramatically increased in recent years, which make significant economic burden for patients and their families. …”
Section: Discussionmentioning
confidence: 99%